Need Analysis of Pre-Laboratory Development to Support Experimental Activities in Science Learning - Marfuatun Marfuatun; Riandi Riandi (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this study was to identify the implementation of the experimental method in science learning and the obstacles faced by teachers, as well as to identify the application of pre-lab in science learning. Research design was survey which is non-experimental quantitative research. The participants were 26 teachers who teach subjects in the sciences, namely Chemistry, Biology, Physics, and Science as integrated subjects. Data were collected through online questionnaires using google forms and were analyzed descriptively. The results show that experimental activities have not been fully applied to science learning. Most teachers provide the tools and materials needed in learning activities in the laboratory and provide work procedures to students. The constraints that are faced by teachers in applying the experimental method are related to facilities and infrastructure, student characters, and experiment time allocation. Most of the teachers have also carried out pre-lab activities, but they are still dominated by lectures from the teacher. This study also explored the pre-lab model to be developed, almost all teachers agreed if the pre-lab was developed in the form of virtual learning. The forms of media that teacher’s interest in for pre-lab activities are videos and android applications